Metode Direct PCR yang Cepat dan Hemat Biaya untuk DNA Barcoding Anggrek Obat Dendrobium crumenatum Sw. - Yusfi Afidah; Mukhamad Su'udi (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2024)
This study aims to develop a rapid and cost-effective Direct PCR method for amplifying the rbcL gene without requiring DNA isolation, particularly for Dendrobium crumenatum Sw., an orchid species known for its traditional medicinal uses. The method involved soaking fresh leaves of D. crumenatum in TE buffer, followed by incubation at 55ºC. The incubation product was Directly used as a PCR template. The results showed a clear DNA band of 600 bp, corresponding to the target rbcL gene. BLAST analysis confirmed that the DNA sequence shared 84-85% identity with other species in GenBank. In conclusion, the Direct PCR method proved to be effective for DNA barcoding applications, offering advantages in speed and cost-efficiency over conventional DNA isolation methods. Keywords: Medicinal Orchids, Dendrobium crumenatum Sw., Direct PCR, DNA Barcoding